REGULATION OF THE TERMS OF TEXTILE AND LIGHT INDUSTRY (Scientific journal of the Fergana State University, 2023)
In this article the need to revise standard textile and light industry terminology is being argued. The article discusses the concept of the “term” from a structural point of view. Examples are given of the views and opinions of a number of linguists on the problem of standardizing textile terminology, overcoming the “incompatibility” between linguistics and the description of technology.